COVID-19 with kidney disorders in Dustira Hospital - Y Kusmala, Yudith; Linasari, Desy; K Nissa, Fitria (ACTA Medical Health Sciences, 2023)
Corona virus diseases-19 (COVID-19) affects the respiratory system and the kidneys. Kidney disorders manifestations in COVID-19 patients are AKI, AKI superimposed chronic kidney disease (CKD), and COVID -19 in CKD sufferers on hemodialysis. The SARS CoV-2 virus can cause deterioration and decline in kidney function because it can bond with angiotensin converting enzyme 2 (ACE-2) receptors on the surface cells of the kidney. This study is a descriptive cross-sectional study that aims to know the profile of kidney abnormalities in COVID -19 patients treated at Dustira Hospital based on the description of age, sex, type of kidney disorder, therapy, and outcome of therapy. This study takes the total sampling data in the form of medical record data from January to December 2021. During this time 275 samples were obtained. Research results show the average age of patients is 57 + 13.5 years. The majority of the patients were male (58.5%). The highest percentage of diagnosed kidney disorders in COVID-19 patients was AKI-superimposed CKD (38.2%). 53.5% COVID-19 patients with kidney disorders received conservative therapy, while 46.5% received hemodialysis With 68.7% conservative therapy and 77.3% hemodialysis, the majority of Covid-19 patients with kidney disorders were able to survive. The study concludes that COVID-19 with kidney disorders is most common in elderly men (>55 years), with the most cases developing AKI-superimposed CKD.  There were a lot of patients who receive conservative therapy but endure life, and many have therapy action hemodialysis, resulting in a higher survival rate. DOI : 10.35990/amhs.v2n2.p54-62 REFERENCE Krishnan A, Hamilton JP, Alqahtani S, Woreta TA. Covid-19: an overview and clinical update. World J Clin Case. 2021;9(1):1–17. Sugihantono A, Burhan E, Samuedro E, Aryati, Rinawati W, Sitompul PA. Pedoman pencegahan pengendalian Coronavirus Disease (Covid-19). 5th ed. Jakarta: Kemenkes RI; 2020. p. 2–214. Kementerian Kesehatan RI. Taktis praktis antisipasi gelombang ketiga Covid-19. Jakarta: Kemenkes RI; 2022. p. 1–26. World Health Organization. WHO Coronavirus (COVID-19) Dashboard [Internet]. [cited 2022 Oct 12]. Available from: https://covid19.who.int/ Kementerian Kesehatan RI. Infeksi Emerging Kementerian Kesehatan RI [Internet]. [cited 2022 Oct 12]. Available from: https://covid19.kemkes.go.id/ Pusat Informasi dan Koordinasi COVID-19 Jawa Barat [Internet]. [cited 2022 Oct 12]. Available from: https://pikobar.jabarprov.go.id/ Pranarka K, Andayani R. Ilmu Penyakit Dalam. 6th ed. In: Setiati S, Alwi I, Sudoyo AW, Simadibrata M, Setiyohadi B, Syam A, editors. Jakarta: Interna Publishing; 2018. p. 3782–6. Cheung AK, Chang TI, Cushman WC, Furth SL, Hou FF, Ix JH, et al. KDIGO 2021 clinical practice guideline for the management of blood pressure in chronic kidney disease. Kidney Int. 2021;99(3):S1–87. Serfozo P, Wysocki J, Gulua G, Schulze A, Ye M, Liu P, et al. Ang II conversion to angiotensin-(1-7) in the circulation is POP-dependent and ACE2-independent. Hypertension. 2020;75(1):173–82. Migliaccio M, Mauro M, Ricciolino R. Renal involvement in Covid-19: A review of the literature. DovePress. 2021;14:895–903. Cruz NAN, Oliveira LCG, Silva Junior HT, Pestana OM, Casarini DE. ACE2 in the pathogenesis of renal abnormalities in COVID-19 patients. Front Physiol. 2021;12(8). Novianty D. Gagal ginjal akut sebagai komplikasi Covid-19: literature review. Indones J Nurs Health Sci [Internet]. 2021;2. Available from: http://jurnal.globalhealthsciencegroup.com/index.php/IJNHS Pasaribu SMR. Badai sitokin COVID-19. Jurnal. 2021;11:224–30. Rabaan AA, Al-Ahmed SH, Muhammad J. Role of inflammatory cytokines in COVID-19 patients: a review on molecular mechanisms, immune functions, immunopathology and immunomodulatory drugs. Vaccines. 2021;9(5):436. Martinez-Rojas MA, Vega-Vega O, Bobadilla XNA. Is the kidney a target of SARS-CoV-2? Am J Physiol Renal Physiol. 2020;318(6):F1454–62. Li G, Fan Y, Lai Y, Han T, Li Z, Zhou P, et al. Coronavirus infections and immune responses. J Med Virol. 2020;92(4):424–32. Upadhana PS, Sastrawan IGGS, Cahyarini IGAAC, Umam AK, Putri ATD, Adhyatma IGR, et al. Kidney disease and its impact on COVID-19 patients at Sanglah Hospital Denpasar. Intern Med Commons. 2022;9(1):23–7. Nurchayati S, Sansuwito TB, Rahmalia S. Gambaran deteksi dini penyakit gagal ginjal kronik pada masyarakat Kecamatan Tambang, Kabupaten Kampar. 2018;9(1):11–8. Siagian KN, Damayanty AE. Identifikasi penyebab penyakit ginjal kronik pada usia di bawah 45 tahun di Unit Hemodialisis RS Ginjal Rasyida Medan Tahun 2015. Anat Med J [Internet]. 2018;1(3):159–66. Available from: http://jurnal.umsu.ac.id/index.php/AMJ Fernández-Ayala DJM, Navas P, López-Lluch G. Age-related mitochondrial dysfunction as a key factor in COVID-19 disease. Elsevier. 2020;142(1). Xiang HX, Fei J, Xiang Y, Xu Z, Zheng L, Li XY, et al. Renal dysfunction and prognosis of COVID-19 patients: a hospital-based retrospective cohort study. BMC Infect Dis. 2021;1–7. Wray S, Arrowsmith S. The physiological mechanisms of the sex-based difference in outcomes of COVID-19 infection. Front Physiol. 2021;12:1–12. Xu Z, Zhang Y, Zhang C, Xiong F, Zhang J, Xiong J. Clinical features and outcomes of COVID-19 patients with acute kidney injury and AKI on CKD. 2022;13(3):884–98. Serfozo P, Wysocki J, Gulua G, Schulze A, Ye M, Liu P, et al. Ang II conversion to Ang-(1-7) is POP-dependent and ACE2-independent. Hypertension. 2020;75(1):173–82. Available from: https://pubmed.ncbi.nlm.nih.gov/31786979/ Haryanti IAP, Nissa KT. Terapi konservatif dan terapi pengganti ginjal pada gagal ginjal kronik. Med J Lampung Univ. 2015;4(7):49–54. Burhan E, Dwi Susanto A, Nasution SA, Ginanjar E, Pitoyo CW, Susilo A, et al. Pedoman Tatalaksana Covid-19. 2nd ed. Jakarta: PDPI, PERKI, PAPDI, PERDATIN; 2020. p. 1–112. Suhardjono, Dharmeizar, Lidya A, Nainggolan G, Marbun MBH, Suginarti, et al. Pedoman pelayanan hemodialisis di sarana pelayanan kesehatan. Jakarta; 2008. p. 1–64. Hakami A, Badedi M, Elsiddig M, Nadeem M, Altherwi N, Rayani R, et al. Clinical characteristics and early outcomes of hospitalized COVID-19 patients with end-stage kidney disease in Saudi Arabia. Int J Gen Med. 2021;14:4837–45. Cheng Y, Luo R, Wang K, Zhang M, Wang Z, Dong L, et al. Kidney disease is associated with in-hospital death in COVID-19 patients. Kidney Int [Internet]. 2020;97(5):829–38. Available from: https://doi.org/10.1016/j.kint.2020.03.005 Legrand M, Bell S, Forni L, Joannidis M, Koyner JL, Liu K, et al. Pathophysiology of COVID-19-associated acute kidney injury. Nat Rev Nephrol. 2021;17(11):751–64. Almeida DC, Franco MDCP, Santos DRP, Santos MC, Maltoni IS, Mascotte F, et al. Acute kidney injury: incidence, risk factors, and outcomes in severe COVID-19 patients. PLoS One. 2021;16(5):e0251042.